2021
DOI: 10.3390/su131810095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Total Quality Management (TQM) Dimensions on Innovation—Evidence from SMEs

Abstract: This research study aims to study and identify which dimensions of TQM have influence on and support innovation strategies within the Portuguese small and medium enterprises (SMEs), in the context of products or services’ innovation and process innovation, as well as to analyze the extent to which this relationship occurs. To examine the linkage between TQM dimensions and innovation strategies, concerning innovation products and innovation processes, a multiple linear regression analysis was chosen and an eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
4
13
0
Order By: Relevance
“…Organizations have extensively adopted TQM as a concept for ensuring the quality of products and services, efficiency, and customer satisfaction [91]. TQM is generally regarded by quality managers and experts as a quality strategy of management [6], and it has played an important role in the evolution of management practices [92]. TQM implementation in IBS projects will significantly benefit the construction sector and stakeholder interactions.…”
Section: Benefits Of Tqm Implementation In Ibs Construction Projectsmentioning
confidence: 99%
“…Organizations have extensively adopted TQM as a concept for ensuring the quality of products and services, efficiency, and customer satisfaction [91]. TQM is generally regarded by quality managers and experts as a quality strategy of management [6], and it has played an important role in the evolution of management practices [92]. TQM implementation in IBS projects will significantly benefit the construction sector and stakeholder interactions.…”
Section: Benefits Of Tqm Implementation In Ibs Construction Projectsmentioning
confidence: 99%
“…Several studies that have focused on the role of TQM in competitive advantage have shown that its implementation promotes better performance and greater competitiveness ( Terziovski and Samson, 1999 ; Zhang, 2000 ; Texeira-Quirós and Justino, 2013 ; Texeira-Quirós et al, 2013 ; Antunes et al, 2017 , 2018a ). The application of TQM principles in HEIS has recently emerged, framed in new realities that began to recognize HEIs as profitable organizations ( Antunes et al, 2018a , 2020 , 2021 ). In this framework, there is a need for differentiation from other HEIs, justifying the increasing implementation of TQM practices ( Nasim et al, 2020 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Many of the researches that have focused on TQM’s repercussions on competitive advantage have shown that their presence leads to improved performance and increased competitiveness ( Terziovski and Samson, 1999 ; Zhang, 2000 ; Texeira-Quirós and Justino, 2013 ; Texeira-Quirós et al, 2013 ; Antunes et al, 2017 , 2018b , 2021 ). In this sense, the following hypotheses of the research were defined:…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The result of this study that TQM affect employee productivity has been confirmed by. Antunes et al (2021) that if the company implements TQM, they can reduce defects, costs, and waste, and improve production processes that help companies achieve higher productivity levels and increase profits.…”
Section: Hypothesismentioning
confidence: 99%